THE SUMMARY OF JASMANI AND THE SPIRIT OF A MUSLIM FACING THE COVID-19 PLAGUE. - Asabah Nurul Hikmah; Partono Partono Partono (Tarbawy : Jurnal Pendidikan Islam, 2020)
THE SUMMARY OF JASMANI AND THE SPIRIT OF A MUSLIM FACING THE COVID-19 PLAGUE. This research writing aims to determine the responses, attitudes and actions of a Muslim in facing of the covid-19. The focus of this research problem is how the form of physical and spiritual endeavors carried out by a Muslim in the face of the covid-19 pandemic. This type of research is a qualitative research with a descriptive qualitative approach. The results showed that understanding of the prevention of covid-19 by a Muslim must be followed by physical and spiritual endeavors. Both physical and spiritual endeavors, have their respective forms and ways. The most important thing from the two endeavors is that both must be carried out in a balanced and wholehearted manner for the common good.